The Roman catastrophe of 1527 in the Italian Wars, or Sacco di Roma: analysis of the historical interpretation of the event by several contemporaries - Pavlov Kirill Vladimirovich (Studia Humanitatis)
The study analyses the perception of historical event contemporaries that represents a “perfect myth” from its accomplishment: the Roman catastrophe in the Italian Wars of 1527, or “Sack of Rome” (Sacco di Roma), when the troops of the Habsburg Empire occupied Rome and forced Pope Clement VII to flee the city. The author has tried to base his selection of historical evidence on three fundamentally important characteristics: belonging to the contemporaries of Sacco di Roma, the origin of these contemporaries from different regions of Italy and the presence of an attempt at reflexive comprehension (or, in the language of modern historical science, historical interpretation) with an attempt to answer the question: “What is the cause of the catastrophe of Rome in 1527?”. As a result of considering both a number of sources and their historiographical analysis in the discourse of intellectual history the author concludes that the most logically compromising reflection of what happened around Sacco di Roma was made by the Florentine diplomat and historian of the Italian Wars era, Francesco Vettori, who pointed out the crisis of the institution of the papacy in the Italian politics of his time. As an appendix to the study, there is a translation from Italian into Russian of Vettori’s dialog fragment by the same name “Sacco di Roma”, in which the diplomat expresses his ideas about the papacy through the mask of a fictional character – the Florentine Antonio.